Student-centred problem-based learning as a transformative approach to legal education - Koraan, Rene Hilary Cheryl-Anne (The IIE, 2017)
The quality of LLB graduates is causing an outcry among members of the legal profession. Concerns that law graduates are poorly prepared to meet the demands of practice and do not possess the legal skills expected of them have surfaced throughout the legal profession. Problem-based learning (PBL) is an instructional method that provides students with the knowledge and skills suitable for problem solving. Student-centred problem-based learning (SPBL) is a combination of problem-based and reiterative problem-based learning. In this paradigm students aim to understand and resolve a problem with which they are faced. Confronting students with practical scenarios and placing them in an appropriate environment (like a mock trial) may result in the students remembering and applying in practice what they have learnt in theory. This could arguably make for a law graduate with the skills required for practice. This paper discusses the LLB dilemma and the impact thereof on the legal profession. It describes the relevant pedagogical approach, which entails that the students continue to learn throughout the rest of their personal and professional lives. It also explores the use of mock trials (as a SPBL method) as a transformative approach to enhancing the development of the skills needed for practice.
Keywords: Quality of graduates; LLB; Legal profession; Mock trials; Problem based learning; Student centered learning; Reiterative prolem-based learning